Link and Match of Tourism Development towards Optimization of Community Empowerment for the Sake of Spatial Utilization - MARLINA, Endy; HERMAWAN, Arief; HERAWAN, Tutut (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
This paper presents an iintegrated manager model as a model of tourism development applied in Bejiharjo village, Gunungkidul Regency, Indonesia. This model is an implementation of tourism development synergy involving the community as the main actor of tourism development and government and private sectors as supporters. The distribution role in this model shows that the community is able to independently lead the spatial development productively within the framework of increasing welfare. In the context of the development of tourist destinations, this model is a synthesis of several development models which includes the model of development of a tourist attraction, model of infrastructure development, model of development of public facilities, model of development of tourism facilities, as well as model of integrated and sustainable community empowerment. This tourism development model is found in the research of Geosite utilization which becomes the most pivotal resource in Bejiharjo village as a tourist attraction. The patterns of space utilization are mapped by phenomenological method to capture the aspirations and development plans of space inductively. Through an in-depth interview and the response to the space the public's view of space was revealed.